Penerapan SOA menggunakan Enterprise Service Bus pada Proses Pengecekan Status Perizinan Pemerintah Kabupaten Sleman - Kabul Kurniawan; Ahmad Ashari (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
The Implementation of web services using point-to-point method considered to be irrelevant weather the number of services are growing up rapidly and more complex. In the other hand, the differences of web service implementation standard is also being a serious problem when the integration and communication among web services are needed.One way that can be applied to provide management information system integration among others is the implementation of Enterprise Service Bus (ESB). ESB is an infrastructure that can be the solution of n-to-n integration complexity problem. ESB concept strongly supports the implementation of Service Oriented Architecture (SOA).This research will discuss about the implementation of ESB in government area, especially in Sleman, sub-district of Daerah Istimewa Yogyakarta local government, Indonesia. Some of ESB functionality such as Routing and Transformation are applied to solve the integration problem between Government to Public (G2P) in case of checking lisence process at Badan Penanaman Modal dan Izin Terpadu (BMPT) Sleman Sub-Distric. The results show that the ESB can be used as the mediator of information integration in case of checking lisence process. Beside that, the results of performance testing shows that the average execution time (AET) for service operations reach up to 0,085 seconds. Furthermore, the system has an average amount of execution about 11.99 times and produces data about 15746.86 bytes or equivalent to 15.38 KB per second. These results indicate that the execution time is considered to be small enaugh so that the services will not interfere the process of the transactions.